Let's talk! : good stuff for girlfriends about God, guys, and growing up - Dobson, Danae (Wheaton, Ill. : Tyndale House, 2003)
Offers "big sister" advice, Christ-centered encouragement, and information for living confidently in today's world.
Let's talk about God -- Let's talk about family -- Let's talk about friends -- Let's talk about guys -- Let's talk about you --Let's talk about eternity.
Keywords: Teenage girls -- Religious life; Christian life; Christian life